2020
DOI: 10.3389/fgene.2020.00054
|View full text |Cite
|
Sign up to set email alerts
|

Spinal Muscular Atrophy in the Black South African Population: A Matter of Rearrangement?

Abstract: Spinal muscular atrophy (SMA) is a neuromuscular disorder, characterized by muscle atrophy and impaired mobility. A homozygous deletion of survival motor neuron 1 (SMN1), exon 7 is the main cause of SMA in~94% of patients worldwide, but only accounts for 51% of South African (SA) black patients. SMN1 and its highly homologous centromeric copy, survival motor neuron 2 (SMN2), are located in a complex duplicated region. Unusual copy number variations (CNVs) have been reported in black patients, suggesting the pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 57 publications
1
12
0
1
Order By: Relevance
“…2% of patients in our cohort. SMN locus rearrangements vary considerably between populations, including the loss of Exons 7–8, which provides a likely explanation for this discrepancy ( Vijzelaar et al , 2019 ; Vorster et al , 2020 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…2% of patients in our cohort. SMN locus rearrangements vary considerably between populations, including the loss of Exons 7–8, which provides a likely explanation for this discrepancy ( Vijzelaar et al , 2019 ; Vorster et al , 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…The architecture of the human SMN locus on chromosome 5q is highly complex due to multiple duplications and inversions and has, therefore, not yet been completely elucidated ( Burghes, 1997 ; Wirth, 2000 ; Rochette et al , 2001 ; Arkblad et al , 2006 ; Lunn and Wang, 2008 ; Thauvin-Robinet et al , 2012 ). Rare intragenic variants in SMN2 have been described ( Prior et al , 2009 ; Bernal et al , 2010 ; Wu et al , 2017 ; Calucho et al , 2018 ; Ruhno et al , 2019 ) that modify disease severity, and it has been suggested that variation within the SMN2 locus, such as deletions of the adjacent NAIP1 , modifies severity ( Burlet et al , 1996 ; Watihayati et al , 2009 ; Amara et al , 2012 ; Ruhno et al , 2019 ; Vorster et al , 2020 ). Variation in the sequence of SMN2 and the SMN locus requires further study in large and well-defined patient cohorts.…”
Section: Introductionmentioning
confidence: 99%
“…Five reports on SMA in sub-Saharan Africans were found, mostly involving South Africans and one each from Congo and Mali (Additional file 2: Table C) [73][74][75]. Several cases from two regions in South Africa reported SMN1-SMA with homozygous loss of exon 7 (± exons 8) ranging between 35 and 100% of their clinical samples, indicating a substantial number of cases with an alternative molecular diagnosis [76][77][78]. An SMN1 gene dosage assay in 300 random black SA samples showed the heterozygote exon 7 deletion in 6 individuals (1/50 population controls; 2%) which was similar to the frequency of SMN1 copy numbers in Kenyans and Nigerians [74], but roughly half of the heterozygote frequency found in European ancestry controls (3-4%) [77].…”
Section: Smn1-sma In Sub-saharan Africamentioning
confidence: 99%
“…Interestingly, the architecture of the SMN region differs substantially between Europeans and Africans, although African-Americans roughly followed the same trends in terms of SMN2 copy numbers as Europeans and Asians [79]. Amongst 75 black South African SMN1-SMA patients, 11% had > 2 SMN2 copies compared with 37% (of 30) SMN1-SMA patients with European ancestry [78]. Taken together, these results underscore the fact that the genetic architecture and disease pathogenic mechanisms in African ancestry individuals may vary from Europeans, and requires further study.…”
Section: Smn1-sma In Sub-saharan Africamentioning
confidence: 99%
“…The first marker in this QTLR (73225) is in the single candidate gene identified here, namely GTF2H2 (General Transcription Factor IIH Subunit 2). GTF2H2 has been linked in human to spinal muscular atrophy [46] and to the neurodegenerative disorder Cockayne syndrome [47]. QTLR P-4 appears to be the prime region for a follow-up finer mapping study.…”
Section: Qtlr P-4mentioning
confidence: 99%